1981
DOI: 10.1039/c39810000621
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of dimesitylsilylene with epoxides. Silanone–epoxide adducts

Abstract: Dimesitylsilylene, generated by photolysis of 2,2-dimesitylhexamethyltrisilane (1) , reacts with epoxides to give dimesitylsilanone-epoxide adducts. M e g MeRECENTLY, considerable interest has been focused on highly reactive unsaturated silicon intermediates.' How-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Furthermore, the C,Si-Si framework is West has proposed a bonding model in which a significant amount of the double-bond character of the disilene is retained in 104c. The large 1J29si-29si coupling constant of 99 Hz measured for 106, which is intermediate between that of disilenes (155 Hz) and disilanes (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70), indicates that the oxadisilirane 104c may be described as a n complex 107. "01i9 l Z 1 l (The 1J29si-29si of cyclotrisilane is small-24 Hz; see Section 4.3.3.…”
Section: Disiliranes and Digermiranesmentioning
confidence: 98%
“…Furthermore, the C,Si-Si framework is West has proposed a bonding model in which a significant amount of the double-bond character of the disilene is retained in 104c. The large 1J29si-29si coupling constant of 99 Hz measured for 106, which is intermediate between that of disilenes (155 Hz) and disilanes (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70), indicates that the oxadisilirane 104c may be described as a n complex 107. "01i9 l Z 1 l (The 1J29si-29si of cyclotrisilane is small-24 Hz; see Section 4.3.3.…”
Section: Disiliranes and Digermiranesmentioning
confidence: 98%
“…[10][11][12][13] Early product-and kinetic studies of the reactions of SiMe 2 with the parent oxirane and various substituted derivatives were interpreted in terms of a multistep mechanism involving the initial formation of a silylene-oxirane complex. [10][11][12]14,15 Tzeng and Weber proposed that the collapse of the complex proceeds via a stepwise mechanism involving a zwitterionic intermediate, in order to account for the formation of siloxacyclohexenes in the reactions of SiMe 2 with vinyl epoxides, in addition to dimethylsilanone and the corresponding diene (eq 2). 11 Various details of the mechanism have received support from subsequent theoretical calculations, [16][17][18] and by recent kinetic studies of the reaction of SiH 2 with oxirane in the gas phase.…”
mentioning
confidence: 99%
“…The present work represents the first experimental study to be reported of the reactivity of simple, transient dialkyl-and diarylgermylenes with oxiranes and thiiranes under neutral ambient conditions, conditions under which the corresponding silylene derivatives react rapidly via formal oxygen or sulfur abstraction to afford the corresponding alkene and silanone [27][28][29][30][31]38 or silanethione, 31 respectively, in good chemical yields. The only related existing studies of the reactivity of Ge(II) systems with substrates of this type are those of Satgé and co-workers, who examined the reactions of a series of amine-coordinated germylenoids with oxiranes and thiirane.…”
Section: Discussionmentioning
confidence: 95%
“…28,29,31 (2) or MeOH, 31 the products of which are formed along with the corresponding alkenes in yields of 50%-70% relative to consumed silylene precursor. Transient silanones have also been shown to react with dienes 27 and oxiranes 30 to form stable products.…”
Section: (1)mentioning
confidence: 99%
See 1 more Smart Citation